Long-term deprescription in chronic pain and opioid use disorder patients: Pharmacogenetic and sex differences - Muriel Javier; Escorial Mónica; Margarit César; Barrachina Jordi; Carvajal Cristian; Morales Domingo; Peiró Ana M. (Acta Pharmaceutica)
More than half of patients with opioid use disorder for chronic non-cancer pain (CNCP) reduced their dose through a progressive opioid withdrawal supported by a rotation to buprenorphine and/or tramadol. The aim of this research is to analyse the long-term effectiveness of opioid deprescription taking into account the impact of sex and pharmacogenetics on the inter-individual variability. A cross-sectional study was carried out from October 2019 to June 2020 on CNCP patients who had previously undergone an opioid deprescription (n = 119 patients). Demographic, clinical (pain, relief and adverse events) and therapeutic (analgesic use) outcomes were collected. Effectiveness (< 50 mg per day of morphine equivalent daily dose without any aberrant opioid use behaviour) and safety (number of side-effects) were analysed in relation to sex differences and pharmacogenetic markers impact [OPRM1 genotype (rs1799971) and CYP2D6 phenotypes]. Long-term opioid deprescription was achieved in 49 % of the patients with an increase in pain relief and a reduction of adverse events. CYP2D6 poor metabolizers showed the lowest long-term opioid doses. Here, women showed a higher degree of opioid deprescription, but increased use of tramadol and neuromodulators, as well as an increased number of adverse events. Long-term deprescription was successful in half of the cases. Understanding sex and gender interaction plus a genetic impact could help to design more individualized strategies for opioid deprescription.